PENGARUH KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK: STUDI KASUS PAJAK BUMI DAN BANGUNAN DI DESA GANDAYASA, KECAMATAN CIKEUSAL, KABUPATEN SERANG, DENGAN PENDAPATAN WAJIB PAJAK SEBAGAI VARIABEL PEMODERASI - Ulfi Jefri; Sukrani Sukrani; Amyati Amyati (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The aim of this research is to determine the effect of mandatory tax awareness and tax sanctions on mandatory tax compliance, with taxpayer income participating as a moderating variable. Land and Building Tax (PBB) revenue in Gandayasa Village shows a low level, reflecting the promise of taxpayer compliance. Factors that contribute to the low level of compliance are low tax awareness, tax sanctions that do not have a deterrent effect on taxpayers, and low taxpayer income. The research method used was a survey method with a quantitative approach involving 2,380 Taxpayers sourced from land and building tax revenue data in Gandayasa Village. Sampling was carried out using the Simple Random Sampling technique, which resulted in 96 samples. The research results show that taxpayer awareness has a significant influence on taxpayer compliance, as evidenced by the t-value of 3.679 ≥ t-table of 1.9858 with a significance level of 0.000. Tax sanctions also have a significant influence on taxpayer compliance, with a calculated t-value of 4.810 ≥ t-table of 1.9858 and a significance of 0.000. Meanwhile, taxpayer income does not moderate the influence of taxpayer awareness on taxpayer compliance, as evidenced by the t-value -1.141 ≤ t-table, with a significance level of 0.151. Likewise, taxpayer income does not moderate the effect of tax sanctions on taxpayer compliance, with a calculated t-value of 1.278 which is smaller than the t-table and a significance of 0.205